2018
DOI: 10.2478/folmed-2018-0005
|View full text |Cite
|
Sign up to set email alerts
|

Anthropological Characteristic of the Distribution of Adipose Tissue in Bulgarian Females with Type 2 Diabetes Mellitus

Abstract: Background: The complex study of adipose tissue in women with type 2 diabetes mellitus (T2DM) is of importance for the clinical course and prognosis of the disease. Aim: To study the distribution of adipose tissue in Bulgarian females with T2DM. Patients and methods: The study included 92 women with T2DM (age range 40-60 years). The control group consisted of 40 age-matched women. Measurement parameters: height, weight, 9 skinfolds (sf) – sfTriceps, sfBiceps brachii, sfForearm, sfSubscapular, sfXrib, sfAbdomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Also, Surendar et al [ 21 ] observed the skinfold measurements of trunk fat were higher in the South Indian people with parental history of diabetes than those with no parental history. Moreover, measuring the skinfold thickness over multiple body sites in 40–60 year-old Bulgarian women found the diabetic females presented primarily upper torso fat distribution and less so in the limbs comparing to the healthy females [ 22 ]. In our study, we assess the body fat distribution via calculating the ratio between peripheral skinfold (tricep or thigh skinfold) and android skinfold (sum of abdominal and suprailiac skinfolds).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Surendar et al [ 21 ] observed the skinfold measurements of trunk fat were higher in the South Indian people with parental history of diabetes than those with no parental history. Moreover, measuring the skinfold thickness over multiple body sites in 40–60 year-old Bulgarian women found the diabetic females presented primarily upper torso fat distribution and less so in the limbs comparing to the healthy females [ 22 ]. In our study, we assess the body fat distribution via calculating the ratio between peripheral skinfold (tricep or thigh skinfold) and android skinfold (sum of abdominal and suprailiac skinfolds).…”
Section: Discussionmentioning
confidence: 99%
“…It was performed via pinching the subcutaneous skinfold in different sites and measuring the thickness with specialized calipers. Studies have revealed it is appropriate for comparing regional adiposity [ 20 22 ]. Several equations have also been developed for calculating BF% using the raw data of skinfold thickness under the assumptions that majority of adipose tissues were located in the subcutaneous area and the body fat is equally distributed over the body [ 23 – 26 ].…”
Section: Introductionmentioning
confidence: 99%